JENIS DAN BENTUK METAFORA DALAM KISDAP “JULAK AHIM” KARYA JAMAL T. SURYANATA - Siti Jamzaroh (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
This research is aimed to find out 1) to know the type of metaphor of Kisdap "Julak Ahim" (2) to describe the metaphoric function in that contained in Kisdap "Julak Ahim" The method used in this research is qualitative descriptive. Data collection is done by reading technique and record technique. Furthermore, the data are classified based on the metaphorical characteristics shown. Data analysis is done by contrasting the expression data used with the metaphor. The results found are: 1) The type of metaphor found based on 1.1) its constituent elements in kisdap "Julak Ahim" is a) the animal metaphor (2); b) the synesthesia metaphor (1); c) anthropomorphic metaphor (2); and d) concrete-abstract metaphor (2); 1.2) based on its structure, there are a) subjective and complementary nominative metaphors and b) sentence metaphors.